Predicting consumer acceptance ratings of cracker-coated and roasted peanuts from descriptive analysis and hexanal measurements - Grosso, Nelson Rubén (2002)
A consumer test, descriptive analysis, and hexanal measurements were performed in cracker-coated peanuts (CCP) and roasted peanuts (RP) to determine the cut-off point for acceptability of stored CCP and RP. Regression analysis showed that roasted peanutty, oxidized and painty flavors and hexanal content were good predictors (R2 ≥ 0.70) of overall acceptance and flavor ratings. A hexanal content higher than 5.39 μg/g in CCP and 7.40 μg/g in RP, and/or an oxidized flavor intensity higher than 27.4 in CCP and 36.2 in RP is expected to have a product unacceptable to consumers (overall acceptance of 5 or lower). These values can likewise be used to determine the endpoint of shelf life of the products.